Auditing IPLs—using safety critical functions manuals. Issue 3 (27th August 2014) - Sellers, Alex J.; Schmidt, Michael S.
<x xml:space="preserve">Abstract</x> The three criteria for an independent layer of protection (IPL) are effectiveness, independence, and auditability. The effectiveness and independence of an IPL typically are evaluated as part of a Layer of Protection Analysis (LOPA), and normally are confirmed by the time the LOPA is finalized. Auditability, on the other hand, is typically not addressed during the LOPA, and frequently is not addressed until someone is charged with the task of actually auditing the IPL, assuming that even occurs. For a Safety Instrumented Function (SIF) with a Safety Integrity Level to be installed in a Safety Instrumented System (SIS), the requirements for auditing are listed in the standards such as IEC 61511 and ANSI/ISA S84 and the relevant information is contained in a Safety Requirements Specification (SRS). However, an SRS for an SIS does not address IPLs that are not SIFs: administrative functions, noninstrumented functions, and nonrated control functions, even though they are also critical to assuring sufficient risk reduction for specific hazards. The auditability, and hence the auditing, of IPLs not installed in an SIS too often becomes an afterthought. A Safety Critical Functions Manual (SCFM) can pick up where the SRS leaves off. It defines requirements for testing, maintenance, and training for IPLs not included in the SIS. The very act of creating an SCFM forces the issue of auditability to be addressed, and defines the items that need to be audited. While an SCFM could manifest itself in different ways, it generally can be expected to include datasheets which address the operation, testing, maintenance, and training requirements for each safety critical function. Although it would be analogous to an SRS, an SCFM typically would be simpler. The article includes a discussion of an approach to SCFMs that has been successful at a number of different organizations for documenting and maintaining those safety critical IPLs that are not already covered by one of the SIS standards. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 228–236, 2015